Leadership style, corresponding policies and staff performance : a study of the agricultural development fund (adf) in Riyadh - Mshel, Altemyat Hawas (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
The main objective of this study is to examine the relationship between leadership style and staff performance in the Agricultural Development Fund (ADF) in Saudi Arabia. The data for the study is obtained from both secondary and primary sources. The secondary sources are text books, journals and other published materials related to the study, while primary sources include questionnaires and interviews. Two methods of data collection are used, that are questionnaire and interview. The researcher distributed questionnaires to all (373) ADF staff, of which 305 were completed. A total of 23 were filled by managers at different levels while 282 were completed by subordinate staff. Subordinate staff rated their leaders' leadership style and also leaders rated themselves on their leadership style in the same questionnaire. Additionally, subordinates rated themselves on their performance. Also, interviews were conducted with leaders and subordinates to supplement the data that were collected by questionnaires. The survey was administered between May and August, 2011. The data collected through questionnaires were analyzed with the assistance of the Statistical Package for Social Sciences (SPSS) Pearson Product Moment and linear regression to establish the relationship between independent and dependent variables. However, the results show that there are significant relationships among staff performance and leadership attributes, namely, skills, nature of communication, contingent reward, behavior, trust, delegation and work habit. The study findings also reveal that some leaders in ADF exhibited a mixed attributes of transactional and transformational leadership styles and leadership in the ADF shows inability in coaching and teaching their subordinates. It is also found that leaders in the ADF treat their subordinates as a group rather than as individuals and the habit of the delegation of authority is not so much practised by leaders in ADF. The study also finds that leaders at ADF play a big role in engaging in personnel practices and managerial policies. Their managerial policies aim at ensuring suitable staff are recruited and pay their dues accordingly. It is further found that leaders provide programmes and incentives to encourage staff commitment and avoid staff alienation. The results of the study show that leaders at ADF use different means such as paying a good salary, incentive for better performance etc. to motivate staff. Also the research reveals that existing personnel and managerial practices at ADF have a positive influence on staff performance in ADF. It is further found that there is a negative relationship between some leadership attributes and variables of staff performance. The correlation analysis reveals that there is a negative relationship between skill and extra effort; nature of communication and extra effort and job satisfaction; contingent reward and extra effort; behavior and extra effort and job satisfaction; trust and extra effort; delegation and job satisfaction; work habit and job satisfaction. Also this study demonstrates that leadership styles are very important affecting staff performance at ADF. The study concludes that a mix of transactional and transformational leadership styles used by leaders at the ADF have influence on staff performance, also it is clear that styles of leadership affect staff performance positively and leadership attributes are good predictors of staff performance.